The effect of pre‐treatment with transcutaneous electrical acupoint stimulation on the quality of recovery after ambulatory breast surgery: a prospective, randomised controlled trial. (28th May 2014) - Zhang, Q.; Gao, Z.; Wang, H.; Ma, L.; Guo, F.; Zhong, H.; Xiong, L.; Wang, Q.
Summary Electroacupuncture has been demonstrated to be effective at alleviating pain and postoperative side‐effects. Our aim was to investigate whether transcutaneous electric acupoint stimulation, a low‐skill alternative to needle‐based electroacupuncture, could improve the quality of recovery after ambulatory surgery. Seventy‐two women scheduled for cosmetic breast surgery were randomly allocated to transcutaneous electric acupoint stimulation or sham groups. Patients in the transcutaneous electric acupoint stimulation group received 30 min of electrical stimulation at three acupoints located on the hand and forearm before the induction of general anaesthesia. We found significant mean (SD) differences between the transcutaneous electric acupoint stimulation and sham groups in the mean (SD) length of recovery room stay (35.6 (12.9) min vs 48.3 (16.3) min, p = 0.01), time to removal of the laryngeal mask airway (10.2 (2.5) min vs 17.8 (4.4) min, p = 0.01), and time to reorientation of the patient (14.6 (3.2) min vs 26.5 (5.0) min, p = 0.01). Further, postoperative pain scores and the incidence of side‐effects were all lower in the transcutaneous electric acupoint stimulation group. In conclusion, transcutaneous electric acupoint stimulation can significantly improve the quality of recovery and decrease the incidence of anaesthesia‐related side‐effects for patients undergoing ambulatory surgery.